What Influences a Career: A Personal Reflection - Donald H. Fairfield (Perspectives of Earth and Space Scientists)
Abstract A scientific career is shaped by factors such as an individual's personality, background, and even uncontrollable exterior factors. Understanding oneself is crucial to one's development as is also the element of luck and being in the right place at the right time. The authors career spanning the development of magnetospheric physics illustrates these points and is described here.